Model Penerimaan Teknologi Belajar Membaca Anak Usia Dini Berdasarkan Konsep TAM - Dwi Marlina (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
Transportation of education through the use of technology can support educators’ task and stimulate interest in learning among students. This research is conducted to find out the factors that influence whether Interactive Learning to Read Software for Early Childhood is well received by its users or not and to determine the causal relationship among the factors that affecting the acceptance of such software. The model used to determine the acceptance of the software Learn How to Read for Early Childhood is TAM (Technology Acceptance Model). TAM explains in detail the model of information technology acceptance with a certain dimension that can affect technology acceptance by users. This model puts factors of attitude and behavior of each user by using two main variables, namely expediency (usefulness) and ease of use (easy to use). The model of acceptance of Learning to Read Software for Early Childhood software is also influenced by other factors such as: Computer Self Efficacy (CSE), Perception of Ease of Use (PEOU), Perception of Usefulness (PU), Attitude toward Using (ATU), Behavioral Intention To Use (BITU), and Actual System Use (ASU). Statistical test is performed using Structural Equations Modeling (SEM), which are processed by applying software AMOS version 7.0. The result of the research shows that the reading software is well accepted by kindergarten children.